2016
DOI: 10.3400/avd.oa.16-00087
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Venous Thromboembolism in Patients Undergoing Endovenous Laser and Radiofrequency Ablation of the Saphenous Vein

Abstract: Objective: Endovenous laser ablation (EVLA) and radiofrequency ablation (RFA) are safe and effective treatments for varicose veins caused by saphenous reflux. Deep venous thrombosis (DVT) and endovenous heat-induced thrombosis (EHIT) are known complications of these procedures. The purpose of this article is to investigate the incidence of postoperative DVT and EHIT in patients undergoing EVLA and RFA. Methods: The patients were assessed by clinical examination and venous duplex ultrasonography before operatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 16 publications
0
18
0
2
Order By: Relevance
“…14 The follow up protocol enabled identification of the highest number of EHIT possible, which otherwise, with a less meticulous follow up would have been lost. 18 Thromboprophylaxis of EHIT is described with variability in randomised trials and single centre studies. Although EHIT occurred despite the systematic use of LWMH during the peri-operative period, it remained asymptomatic and dissolved in the weeks after the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…14 The follow up protocol enabled identification of the highest number of EHIT possible, which otherwise, with a less meticulous follow up would have been lost. 18 Thromboprophylaxis of EHIT is described with variability in randomised trials and single centre studies. Although EHIT occurred despite the systematic use of LWMH during the peri-operative period, it remained asymptomatic and dissolved in the weeks after the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, EHIT cases were resolved within 2-4 weeks in most patients. 3) EVLA with a 980 nm diode laser fiber (ELVeS) was reported to be a minimally invasive procedure with improved recovery of postoperative venous function compared with air plethysmography and is similar to stripping. 4) Furthermore, the 1470 nm EVLA reduced the postoperative recovery time, wound-related complications, and the incidence of skin disorders, such as ecchymosis and bruising, which was significantly lower than that with a 980 nm diode laser fiber (ELVeS).…”
Section: Discussionmentioning
confidence: 99%
“… 13 16 ) Marsh et al 14 ) reported a low incidence of EHIT post-EVLA, with no differences from RFA. Kurihara et al 17 ) reported that EHITs caused by RFA were mainly class 1 according to the Kabnick classification. All EHITs in our study were class 1 and disappeared without antithrombotic therapy.…”
Section: Discussionmentioning
confidence: 99%